Problematika terminov "prostoživeče", "gojene" in "rejne" živali v slovenski zakonodaji - Žigo Jonozovič, Aleksandra (Acta agriculturae Slovenica, 2007)
Agricultural biodiversity includes, among other, wild animal species that are used or may be used for the production of food. Animals may be farmed or bred for food, wool, leather, furskin or for other economic purposes, but we can also breed them for company, recreation, protection or work. The purpose of farming and breeding is crucial for setting of criteria for handling individual animal or a groupof them. Legal purposes request precise and harmonised terminology. The paper deals with the use of terms such as animals of wild species kept in captivity, bred (game) animals, farmed (game) animals in Slovene regulation. In Slovene legislation there is no single act which holistically regulates breeding and farming of animals of wild species. The use of terms in regulations which partially deal with the subject is not harmonised and does not fully take into consideration the use of animals. The article gives the sugestions for subdivision and use of studied terms as well as changes of some legislation acts. The schematic representation of core differences between terms under consideration is presented.
Keywords: gojenje; predpisi; prostoživeče živali; reja; terminologija; ujetništvo; zakonodaja